Medical Malpractice Insurance: Protecting Patients and Healthcare Professionals - Pandele, Adina Laura (Technium Social Sciences Journal, 2023)
Medical malpractice is a complex and delicate issue, given the fact that errors or negligence in the provision of healthcare services can have serious consequences for the patients. From the patients’ perspective, medical malpractice insurance provides a level of safety and trust in the healthcare system. If they incur damages due to medical negligence, they have the option of seeking compensation through medical malpractice insurance policies. This insurance helps them obtain financial compensation for additional medical costs, further treatment, lost wages, and other damages. On the other hand, healthcare professionals may face allegations of malpractice, even in situations in which their actions were in compliance with professional standards.